Social networks for health communication in rural Uganda: A mixed-method analysis of Dekabusa Trading Centre, Luwero County. Issue 11 (1st November 2020) - de Vries, Daniel H.; Bruggeman, Jeroen; Benoni, Turinawe E.; Rwemisisi, Jude T.; Kashaija, Laban M.; Muhangi, Denis; Kaawa-Mafigiri, David; Pool, Robert
ABSTRACT: To reach the most vulnerable individuals in under-resourced countries, health communication interventions increasingly move towards the community level. However, little is known about how health information spreads through local social networks. This paper maps the health information network of a rural trading centre in Uganda. As part of a five-year ethnographic study of sustainable community health resources, ego networks were obtained for 231 village residents in March 2014. Using both ethnographic and social network data, we analyze how the village social network is structured, and how this structure may influence the transmission of health information. Results show a network with low average proximity, with a small number of individuals, notably key administrative officials, much closer connected to many other community members than average. However, because of social partitioning in the village network, a number of people are outside the social clusters in which the top influencers are located.